Exploration of the Merariq Tradition in Sasak Lombok, Indonesia: Analysis in Islamic Law and Socio-Cultural Dynamics Perspectives - Azwar, Wahyu; Mayasari, Deviana; Winata, Aliahardi; Garba, Malami Muhammad; Isnaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
Indonesia's rich diversity encompasses various ethnicities, cultures, and religions, with deeply ingrained marriage customs such as the Sasak tradition of Merariq, which reflects a delicate balance between Islamic law and socio-cultural dynamics while facing challenges of persistence and extinction in modern times. This study aims to provide an overview of how local wisdom can be explored from various perspectives, particularly within the framework of Islamic law and the socio-cultural dynamics prevalent in Sasak society. This study employs a qualitative approach with a descriptive analysis method. The research involves data collection through observations in Terong Tawah Village, West Lombok, and interviews with various key figures, including youth leaders, customary leaders, religious leaders, and community members. Additionally, documentation related to the implementation of the Merariq tradition in Terong Tawah Village was conducted to ensure the validity of the obtained data. The research findings elucidate that the Merariq tradition still holds cultural significance but has been simplified to align with Islamic teachings. This tradition involves stages such as midang, memaling, nyelabar, akad nikah, sorong serah, begawe, and bejango or nyongkolan. Implementing the Sasak customary wedding ceremony or Merariq must be harmonized with Islamic understanding to ensure compliance with Islamic principles.